Patients with sickle cell disease are frequently excluded from the benefits of transcranial doppler screening for the risk of stroke despite extensive and compelling evidence - Rodrigues, Daniela Laranja Gomes; Adegoke, Samuel Ademola; Campos, Rejane de Souza Macedo; Braga, Josefina Aparecida Pellegrini; Figueiredo, Maria Stella; Silva, Gisele Sampaio (Arquivos de Neuro-Psiquiatria, 2017)
Transcranial doppler (TCD) is a strategic component of primary stroke prevention in children with sickle cell disease (SCD). This study was conducted to examine the TCD characteristics of children with SCD in nine different medical centers in Brazil.Transcranial doppler was performed in accordance with the Stroke Prevention Trial in Sickle Cell Anemia Protocol.Of the 396 patients, 69.5% had homozygous SS hemoglobin. The TCD result was abnormal in 4.8%, conditional in 12.6%, inadequate in 4.3% and abnormally low in 1% of patients. The highest mean flow velocities were 121±23.83cm/s and 124±27.21cm/s in the left and right middle cerebral artery respectively. A total of 28.8% patients (mean age 9.19±5.92 years) were evaluated with TCD for the first time.The SCD patients were evaluated with TCD at an older age, representing an important missed opportunity for stroke prevention. Since TCD screening in patients with SCD is important to detect those at high risk for stroke, it is recommended that this screening should be made more readily available.
Keywords: sickle cell disease; ultrasonography; doppler; transcranial; stroke